PERAN MEDIA MASSA DI AMERIKA SERIKAT DALAM MEMPENGARUHI KEBIJAKAN INVASI KE IRAK PADA TAHUN 2003 - Nurma Juwita, R.A Cintya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 2 (2014), 2014)
ABSTRACK The role of the mass media today not only as a communication tool, but also the mass media took part in influencing the politics and government of a State. The mass media is regarded as one of the tools in determining the foreign policy of a State. In the case of the United States invasion of Iraq, for example, considered the mass media played a role in influencing foreign policy in the United States. Mass media has a role in terms of making an opinion in which it affects the thinking part of the state actors in making decisions related to foreign policy. This is evidenced from the policies of President Bush in 2003, to invade Iraq which is influenced by the news-media reports in the United States on the status of Iraq. From this arises is exactly the view that the role of the mass media today is not only focused as a tool for information only, but also as one of the factors that affect the process of making foreign policy a state actor. Keywords : Mass Media, President Bush's policy, Iraq Invasion